Cassius Dio the Historian : Methods and Approaches - Madsen, Jesper Majbom,; Lange, Carsten Hjort, (Historiography of Rome and Its Empire ;, 2021)
This volume focuses on Cassius Dio as a historian - the only historian who allows us to follow the developments of Rome's political institutions during a more than thousand year period, from the foundation of the city to Cassius Dio's retirement from public life in 229 CE. The volume explores the Roman historian's methodology and agendas, all of which influenced his approaches to Rome's history. It offers a reassessment that rests on a deeper study of his relationship with historiographical traditions as well as his narrative and structural approach to Roman history. It examines Cassius Dio as both a writer in the historiographic tradition with his own agenda for writing The Roman History and a historian with his own ambition to tell the history of Rome.